Livros didáticos: gênero, currículo e ideologia na escola primária - Nicareta, Samara Elisana (2010)
The roles that society sets for women are grown in the cultural environment with the help of the school (LOURO, 2008, 1997; SOUZA, 2005; ROSALDO, 1979). The objective of this research is to identify and discuss the gender question that is present in the images through the textbooks published between 1915 and 1969. The methodology is based on documental analysis of 33 books: textbooks, reading books and manuals of Moral and Civic Education. The image analysis is based on Cunha’s perspectives (2007). Illustrations of the white girl are prominent, wearing dress, beautiful hair, ribbon, always accompanied by toys such as dolls. The girl and woman are represented almost exclusively at home or in situations where there are physical limits and control. In contrast, the boy and man are represented with variation in dress, typically male, located in private and public places, in situations that suggest freedom. In the representations of family, there are two distant subjects divided concerning their parental roles: male and female. The textbook of the Brazilian primary school brings images full of constructed identities, expected behavior or accepted as normal, proposed by a particular ideology. It is clear the curriculum function with an ideological content, attributed to the textbook in history. It is intended to establish and support an educational aim, as a privileged vehicle to inoculate rules, behaviors and social patterns.